Programa de educación sexual para una estudiante con discapacidad intelectual moderada de tercer año de bachillerato de la Unidad Educativa del Milenio Bernardo Valdivieso, 2023 - Macas Ortega, Gabriela Fernanda (2023)
The objective of this degree work was implement a sex education program to improve the student's knowledge and attitudes about sexuality of the student with moderate intellectual disability of the third year of high school of “Unidad Educativa del Milenio “Bernardo Valdivieso'', 2023. A qualitative research of phenomenological, descriptive transverse cut was carried out using the case study method; the prudence test was used, parental fears questionnaire, the psycho pedagogical file, semi-structured interviews and achievement control matrix. In relation with the results, the psychologist state that within their plans they do not have educational activities on sexuality aimed to students with intellectual disabilities, the mother has not participated in a sexuality training for her disabled daughter; the parental fears of both, father and mother, is not having ways, strategies or tools to address sex education and not being able to prevent possible sexual situations or behaviors; within the student's knowledge and attitudes about sexuality there are 5 responses in the "medium" category expressing adequate and conscious understanding of attitudes to be taken in situations of sexual risk; 5 responses are placed in the category of "low" denoting uncertainty or lack of clarity in their understanding in certain circumstances of sexual risk, and 3 responses in the “null” category indicating a lack of knowledge or understanding about how to act in situations that may infringe their sexuality. Thus, it is concluded that psychologists do not have or implement sex education programs for people with intellectual disabilities. Likewise, parents have some fears about the sexual development of their daughter with ID. The student in certain situations of sexual risk has medium, low and no knowledge due to the lack of understanding of situations that can lead to risks. Therefore, the sex education program implemented did achieve to improve knowledge and attitudes in the student with ID that lead to face sexual risk situations